(untitled) (Journal of Humanities and Social Sciences Research, 2023)
If an inactive muscle is stimulated by a series of stimuli, the first few contractions are usually small and disorganized, and the role of relaxation in them is relatively incomplete, then with the continuation of the muscle work, larger contractions follow, i.e. the force of contraction is stronger and the relaxation is complete, and this is due to the warm-up exercises during the first contractions in the muscle The same, during which the wastes of vital activities are formed in the muscle, as well as heat generation, which raises the temperature of the muscle, i.e. (thermal factors and vital wastes) are the ones that work to expand the blood vessels, so the blood supply to the muscle tissues increases due to the blood flow inside the medium blood vessels, and this improves the functional condition The efficiency of the muscle increases due to the arrival of a sufficient amount of oxygen and nutrients carried by the blood. This research discussed the concept of electrical stimulation of the muscle, how it works, and the method of implementing this stimulation in the sports field, leading to the results of the research and a list of sources and references.